The Gǝʿǝz Manuscripts Collection from the Monastery of Däbrä Ṣǝyon (Abunä Abrǝham, Tǝgray, Ethiopia) - Hagos Abrha Abay (Aethiopica)
The monastery of Däbrä Ṣǝyon (Abunä Abrǝham), situated on a peak of the eastern chains of the Gärʿalta mountains, is one of the well-known medieval Ethiopian monasteries. It is said to have been established in the fourteenth century by St Abrǝham of Tǝgray. According to his own gädl, Abunä Abrǝham was not only the founder of the monastery, but was also known to be an active participant and director of the architectural work of the rock-hewn church. It is known that Gärʿalta is endowed with reflections of Aksumite culture, and the monastery of Däbrä Ṣǝyon also seems to have had its own share in its continuation. Many places and monasteries (in Tǝgray) are linked to this monastery in terms of shared monastic culture and land granting. Däbrä Ṣǝyon is a rock-hewn church in which many Christian historical artefacts have been preserved. Among the non-codex written artefacts, it has preserved, in particular, a ṭawos manuscript. Seventy-two Gǝʿǝz manuscripts, most of which of hagiographical and liturgical genre, are kept in the church. All were digitized, foliated, with quire number and structure sorted out in 2018, via a project carried out by the St Yared Center for Ethiopian Philology and Manuscript Studies (SYCEPMS) of Mekelle University. Material, physical, and chemical analysis of the manuscripts was not applied due to a lack of equipment and skill. The manuscripts are now in the process of being catalogued and examined for dating, and the article provides a synthetic survey of the whole collection. The ṭawos manuscript, that is, a peacock-type manuscript from the fifteenth century, is part of the collection; its format calls for consideration regarding the definition and significance of a special style of Ethiopic manuscript culture. As a result, this article aims at introducing the monastery and its manuscript collection.